Generic instantaneous force modeling and comprehensive real engagement identification in micro-milling. (15th June 2020) - Zhang, Yu; Li, Si; Zhu, Kunpeng
Highlights: A new and generic instantaneous force model in micro milling is established, in which the size and tool runout effects are reflected. The real cutter-workpiece engagements are comprehensively identified with critical position of actual entry and exit angles explicitly determined. The proposed force model is developed and can be obtained conveniently and fast by only once calculation of the AUCT with inclusion of tool run out effect. The theoretical forces obtained from the proposed model are compared and validated with experimental data. Abstract: Cutting force modelling has been one of the most important tools for understanding the dynamics and for process control of micro milling. While current studies have widely investigated the uncut chip thickness and tool runout mechanics, they mostly took account a specific case and a general tool engagement determination is yet to be established. These lead to low adaptability and bring difficulties for process modeling and online control. In this study, a new and generic instantaneous force model is developed, in which the size effect is reflected in the force coefficients, and the tool runout effect is included in the instantaneous uncut chip thickness. In the model the real engagement is comprehensively identified under the tool run out effect, with the actual entry and exit angles at the critical position explicitly determined. The average uncut chip thickness (AUCT), actual cutting depth, center position and geometrical relations are analytically established. The proposed force model can be obtained conveniently and fast by only once calculation of the AUCT with inclusion of tool run out effect. With the main influencing factors considered, the force models are computational efficient, good in adaptability and could conveniently be generalized to universal model. Compared to the experimental measurements, the maximum peak errors of the forces are all less than 0.6%, which validates the efficiency and accuracy of the proposed model. Graphical abstract: Image, graphical abstract